2014
DOI: 10.1016/j.tsf.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic nickel oxide films and their compatibility with potassium hydroxide and lithium perchlorate in propylene carbonate: Optical, electrochemical and stress-related properties

Abstract: Electrochromic nickel oxide films and their compatibility with potassium hydroxide and lithium perchlorate in propylene carbonate: Optical, electrochemical and stress-related properties. AbstractPorous thin films of Ir oxide were prepared by reactive dc magnetron sputtering onto unheated substrates. The crystallite size was ~5 nm, and a small amount of unoxidized Ir was present. The electrochromic performance was studied by optical transmittance measurements and cyclic voltammetry applied to films in aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 99 publications
0
37
0
Order By: Relevance
“…The RBS spectra were fitted to a model for the film-substrate system by use of the SIMNRA program [61] . [30,31,62] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RBS spectra were fitted to a model for the film-substrate system by use of the SIMNRA program [61] . [30,31,62] .…”
Section: Methodsmentioning
confidence: 99%
“…The electrochromism of lithium-containing Ni oxide films has been investigated in numerous studies aimed at elucidating basic optical and electrochemical mechanisms [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] as well as to produce counter electrodes for application in W-oxide-based EC devices [5,27,32,[34][35][36][37][38] .…”
Section: + Exchange In Ni Oxide: a Critical Assessmentmentioning
confidence: 99%
“…[1][2][3] These devices normally utilize joint transport of small ions and electrons between a thin film of tungsten oxide and a counter electrode based on nickel oxide, basically in the same way as in an electrical battery, and the optical transmittance is low when the charge resides in W oxide while the transmittance is high when the charge is in Ni oxide. Ni oxide films suffer from optical degradation and limitation in modulation span under extended electrochemical cycling, [4][5][6] and several recent studies aimed at alleviating these deficiencies have been reported. Beneficial effects of additives to the Ni oxide have been studied, specifically for Li, 7,8 C, 9,10 N, 11 W, 12 (Li,W), 13 (Li,Al), 14 (Li,Zr), 15 and several more.…”
mentioning
confidence: 99%
“…For example, the degradation of NiO x film tested in KOH electrolyte was already reported after about 1000 cycles, whereas the use of anhydrous lithium perchlorate dissolved in propylene carbonate lengthened the cycling life of this film . However, on the contrary, it was reported that it was possible to reach a value of 10 000 cycles for NiO x film in KOH electrolyte, whereas the use of lithium conducting anhydrous electrolyte yielded very rapid cycling degradation . This problem deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Coloration/bleaching cycles are accompanied by mechanical stresses arising owing to insertion/extraction of ions, such as compressed and tensile stresses reported in ref. . These stresses may destroy the EC film, causing grain fracture and total damage to an EC material.…”
Section: Introductionmentioning
confidence: 99%